2013
DOI: 10.1159/000355484
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Is Not an Independent Risk Factor for Premature Coronary Artery Disease

Abstract: Background/Aim: There is still debate on the role of serum uric acid as an independent risk factor for coronary artery disease (CAD), particularly premature CAD. This study aimed to investigate whether serum uric acid is a risk factor for premature CAD and whether it can influence the severity of coronary artery stenosis. Methods: Candidates for coronary artery angiography (age <45 years for men and <55 years for women) who met the inclusion criteria were enrolled in this study. Clinical data of the patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Zand et al's study only involved 245 EOCAD patients and 228 normal coronary subjects. They found that UA was significantly related to the presence of EOCAD, but it is not an independent risk factor for EOCAD [ 31 ]. Dai and coworkers demonstrated that higher serum UA level might play an important role in the severity of EOCAD in 786 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zand et al's study only involved 245 EOCAD patients and 228 normal coronary subjects. They found that UA was significantly related to the presence of EOCAD, but it is not an independent risk factor for EOCAD [ 31 ]. Dai and coworkers demonstrated that higher serum UA level might play an important role in the severity of EOCAD in 786 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recent study conducted by Okura et al showed that in a cohort of patients (n = 8832) with severe CAD (defined as coronary stenosis ≥75% of lumen obstruction), the SUA level was an independent predictor of cardiovascular events and all-cause mortality during the 3 year follow-up [25]. Nonetheless, some other investigations did not generate similar results [8][9][10]. Till now, the mechanisms generating this association remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple studies have proposed uric acid as a cardiovascular risk factor, there is much controversy concerning the nature of the relation between SUA and CAD susceptibility [8][9][10] due to its close relation to other traditional risk factors involved in CAD [11] such as lipid metabolism, inflammation, and chronic kidney disease. Thus, the exact mechanism underlying the relationship between the SUA level and incident CAD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Increased uric acid levels have, however, also been associated with chronic kidney disease, 59 CV complications 60 and congestive heart failure, 61 although a cause and effect relationship of uric acid and CV outcomes is far from proven. 62 Reduction in levels of uric acid has consistently been seen with SGLT-2 inhibitors, 63 65 presumably mediated by the actions of solute carrier family 2, facilitated glucose transporter member 9 (SLC2A9), also called GLUT9, an urate transporter which secretes urate back into the urine in exchange for glucose. 66 It is entirely unclear whether these uric acid effects might translate into long-term beneficial outcomes on either renal function or macrovascular complications.…”
Section: Potential For Modulation Of Non-glycaemic CV Risk Factors Wimentioning
confidence: 99%